Perbandingan Perubahan Luas Luka dan Angiogenesis pada Jaringan Luka Bakar Derajat IIB Tikus Sprague Dawley yang Diberikan Platelet Rich Fibrin dan Advanced Platelet Rich Fibrin - Kurnia, Shantika Aqilla; Wahyuningsih, Komang Ardi (Jurnal Kesehatan Andalas, 2021)
Burns increase tissue damage by free radicals, thus hindering the healing process. Platelet Rich Fibrin (PRF) and Advanced Platelet Rich Fibrin (A-PRF) are autologous fibrin matrices that contain growth factors and have been proven to increase tissue formation and regeneration. Objectives: To determined the effect of applying PRF and A-PRF on deep second-degree burns. Methods: This study was experimental research on twenty male Sprague Dawley rats were randomly divided into four groups. Group A and B as control groups received NaCl 0,9% and silver sulfadiazine ointment, respectively. Group C was given PRF and group D was given A-PRF. Burns are photographed and the area was calculated using the ImageJ application. After 14 days of therapy, the burn areas were excised and made into histological slides. Microscopic study of angiogenesis was observed using a microscope at 400x magnification. Results: Changes in wound surface area in PRF and A-PRF groups were 3,106 cm and 2,333 cm. The number of angiogenesis in PRF and A-PRF groups were 3.88 and 5.88. The data was analyzed using One-Way Anova and the results showed that there were no significant differences between the changes in the wound area and angiogenesis of PRF and A-PRF groups. Conclusion: This study showed that there are no significant differences in changes in wound surface area and angiogenesis of burn injury after topical application of PRF and A-PRF.Keywords: Â angiogenesis, burn injury, changes in wound surface area, A-PRF, PRF